(untitled) (Research, Society and Development, 2025)
Early childhood represents a crucial period of physical and cognitive development, in which adopting a healthy diet plays a fundamental role in adequate growth and preventing diseases throughout life. The school environment, in turn, offers privileged opportunities for nutritional education, especially through playful and interactive approaches. More recently, artificial intelligence (AI) has stood out as an innovative tool in the creation of educational content, including that aimed at children. In this context, this study aims to report the experience of developing and implementing a nutritional education campaign carried out in public schools in the city of Itabira (MG), with the support of generative AI tools. Materials such as music, a video clip and graphic pieces were developed and used in in-person and digital actions with approximately 400 school-age children. The campaign showed that, even in contexts with limited resources and without prior design expertise, the creative use of AI can enhance the production of attractive, viable content aligned with the children’s universe, favoring engagement in health promotion actions.